Adoption of AI and Digital Technologies in Early-Stage International Student Entrepreneurship: A case study from Vaasa, Finland - Truong, Thuy An (My University, 2026)
As digital technologies and Artificial Intelligence (AI) become increasingly embedded in entrepreneurial activities, their role in shaping nascent ventures has gained growing attention from scholars. For international student entrepreneurs, who often operate under contextual conditions shaped by limited networks, language barriers, and unfamiliar institutional environments, digital technologies may play a particularly significant role in mediating these challenges. While existing literature highlights the potential of digital technologies to reduce barriers and enable entrepreneurship, there remains limited understanding of how these tools are used in early-stage ventures under such conditions. This thesis examines how international student entrepreneurs use digital technologies and AI during nascent and early-stage venture development, drawing on perspectives from mixed embeddedness theory and digital entrepreneurship theories. The study adopts a qualitative approach based on semi-structured interviews and thematic data analysis. The findings show that digital technologies are integrated into key entrepreneurial activities, including customer acquisition, communication, and operations, functioning as essential infrastructure for market participation. In contrast, AI, particularly Generative AI (GenAI), is primarily used in a task-based and non-strategic manner. Overall adoption remains limited in depth and is driven by accessibility, familiarity, and immediate operational needs. The study contributes to the literature by showing that structural constraints are not solely determinative but can be partially mitigated through the interaction of human capital and the practical use of digital technologies and GenAI. The findings highlight the importance of strengthening eco-system support to enhance international student entrepreneurs’ ability to effectively use digital technologies and point to the need for further research on the evolving role of AI in entrepreneurial contexts.
Keywords: digitalisation; technology; digital technology; entrepreneurship; small-scale entrepreneurs; technological development; artificial intelligence; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business